2013
DOI: 10.1038/pr.2013.50
|View full text |Cite
|
Sign up to set email alerts
|

Modeling determinants of growth: evidence for a community-based target in height?

Abstract: Background: Human growth is traditionally envisaged as a target-seeking process regulated by genes, nutrition, health, and the state of an individual's social and economic environment; it is believed that under optimal physical conditions, an individual will achieve his or her full genetic potential. Methods: Using a panel data set on individual height increments, we suggest a statistical modeling approach that characterizes growth as first-order trend stationary and allows for controlling individual growth te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 23 publications
4
27
0
Order By: Relevance
“…The present analyses show that spatial proximity also influences height of infants, children and adolescents of four low and middle‐income countries. This corresponds to evidence from other studies based on modern and historic data obtained in high‐income countries showing that spatial proximity influences height in adults (Aßmann & Hermanussen, ; Bent et al, ; Gomula et al, ; Hermanussen et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present analyses show that spatial proximity also influences height of infants, children and adolescents of four low and middle‐income countries. This corresponds to evidence from other studies based on modern and historic data obtained in high‐income countries showing that spatial proximity influences height in adults (Aßmann & Hermanussen, ; Bent et al, ; Gomula et al, ; Hermanussen et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…In addition to these above mentioned factors, preliminary studies have shown that an individual's height may also be influenced by his or her social peer groups and community (Aßmann & Hermanussen, ). Some of these studies provide an analysis of historic and modern height data of military conscript from Switzerland, Norway and Poland suggest an influence of geographical connectedness on height (Bent, Rybak, & Groth, ; Gomula, Koziel, Groth, & Bielicki, ; Hermanussen, Aßmann, & Groth, ), in which members of the same geographic districts tend to be similar in height, that is, conscripts may be short because young men of the same city and of closely neighboring cities are also short (Aßmann & Hermanussen, ; Gomula et al, ; Hermanussen et al, ). This phenomenon is not only seen in adult height, but also in the height of adolescents; Fourteen year old girls attending the same class within a school are more similar in height compared to 14‐year‐old girls of the same school (Koziel & Gomula, ), indicating that spatial proximity reduces height variability.…”
Section: Introductionmentioning
confidence: 99%
“…Aßmann & Hermanussen (2013) used a Bayesian approach to model data from a longitudinal study of school children and adolescents from Zurich, Switzerland, and found evidence for a growth regulation that operates during adolescence and adjusts individual height toward the average height of their peers, i.e. her/his immediate community (Fig.…”
Section: Social Interactions and Their Effects On Growth In Heightmentioning
confidence: 99%
“…Quite in contrast to the biological and economic concept for the understanding of human growth, recent attention was focussed on the effect of the community on child and adolescent growth and body height [50]. Based on new experimental evidence in animals [51], the concept of social height targeting and strategic growth adjustments was expanded suggesting that stature may be considered a social signal.…”
Section: Normative Growth and Stunting: A Matter Of Definitionmentioning
confidence: 99%